Avaliação histológica e ultra-sonográfica de fígado de cadelas submetidas a programas de ganho e perda de peso - COSTA, Rogério de Oliveira (2008)
The objective of this experiment was to evaluate the histology of livers of castrated bitches during sequential periods of weight gain and loss, through analysis of samples obtained by ultrasound guided biopsies. The experimental groups were composed by 30 bitches submitted to overweight by using of hypercaloric ration, from these animals were selected 14 to be submitted to two differents weight loss programs with seven receiving hypocaloric ration and seven receiving normocaloric ration. Periodic ultrasonographic analysis was employed to evaluate liver structure during the initial, obesity and weight loss stages, and revealed that none of the animals displayed altered images and no lesions at any stages. Histological examination revealed that no animals showed (0%) fibrosis or fat degeneration, 13 animals (92,8%) presented mild inflammation and one animal (7,2%) had severe inflammation. Nine animals (64,2%) did not have any kind of necrosis, four animals (28,5%) had mild necrosis and one animal (7,2%) had moderate necrosis. At the end of obesity stage, no animal showed fibrosis or fat degeneration and all 14 animals had mild inflammation. Ten dogs (71,5%) showed no signs of necrosis and four animals (28,5%) with light necrosis. Finally, in both groups in the weight loss stage no one animal (0%) with fibrosis, fat degeneration or necrosis and 14 animals (100%) with light inflammation. The group 2 had no animal had fibrosis, fat degeneration or necrosis and all dogs showed light inflammation. The results allowed the establishment of comparative parameters between ultrasonographic liver images and histological hepatic analysis in different stages of obesity and weight loss.